THE IMPACT OF INTEGRATED REPORTING ON CORPORATE INFORMATION DISCLOSURE QUALITY: A SYSTEMATIC LITERATURE REVIEW - Lovanka Salsabila Aulia Putri; Yusnaini Yusnaini (Jurnal Media Akademik (JMA), 2026)
This study aims to analyze the influence of Integrated Reporting on the quality of corporate information disclosure through a systematic literature review approach. The increasing demand for transparency and accountability has encouraged companies to adopt Integrated Reporting as a comprehensive reporting framework that integrates financial and non-financial information. This research applies a Systematic Literature Review (SLR) method by analyzing 32 research articles published in various indexed journals. The selected articles originate from several journal index categories, including Scopus (Q1–Q4), national accreditation (Sinta 2–4), ScienceDirect, Garuda and DOAJ. The findings indicate that most previous studies report a positive relationship between Integrated Reporting and the quality of corporate information disclosure. Integrated Reporting enhances transparency, improves the relevance of information, and strengthens communication between companies and stakeholders. Overall, the results suggest that Integrated Reporting plays an important role in improving disclosure quality and supporting better corporate reporting practices.